Optimalisasi Pemanfaatan Perpustakaan untuk Menumbuhkan Minat Belajar Siswa di SMP Negeri 1 Buntulia - Vitrawati Mohamad; Riyanti Ismail; Muh. Wahyuddin S. Adam (Lembaga Pengembangan Kinerja Dosen, 2025)
SMP Negeri 1 Buntulia has adequate library facilities, but it does not affect the intensity of library use by students. Therefore, this study aims to optimize the utilization of the school library at SMP Negeri 1 Buntulia to increase student learning motivation. Considering that the library has great potential as a learning resource and a space for self-development, this study focuses on identifying and implementing effective strategies to increase student involvement with the library. The research method used is a descriptive qualitative approach, with data collection through observation, interviews with the school principal, head of the library, class teacher, and students as well as documentation of library activities.Based on the research results. The researcher concluded that SMP Negeri 1 Buntulia already has facilities and infrastructure to support the learning process. Physically, the Mo'otota library at SMP Negeri 1 Buntulia is decent. It has been equipped with various facilities to foster students' interest in learning. It is proven by the student's ability to answer questions given by the teacher during classroom learning, the student's ability to summarize the reading books that have been read, and the student's initiative in visiting the library.